Targeted SPP1 Inhibition of Tumor‐Associated Myeloid Cells Effectively Decreases Tumor Sizes - Benan Kartal; Christopher S. Garris; Hyung Shik Kim; Rainer H. Kohler; Jasmine Carrothers; Elias A. Halabi; Yoshiko Iwamoto; Anne‐Gaëlle Goubet; Yuxuan Xie; Pratyaksha Wirapati; Mikaël J. Pittet; Ralph Weissleder (Advanced Science)
Abstract Secreted phosphosprotein 1 (SPP1)High tumor‐associated macrophages (TAM) are abundant tumor myeloid cells that are immunosuppressive, pro‐tumorigenic, and have a highly negative prognostic factor. Despite this, there is a lack of efficient TAM‐specific therapeutics capable of reducing SPP1 expression. Here, on a phenotypic screen is reported to identify small molecule SPP1 modulators in macrophages. Several hits and incorporated them into a TAM‐avid systemic nanoformulation are identified. It is shown that the lead compound (CANDI460) can down‐regulate SPP1 in vitro and in vivo and lead to tumor remissions in different murine models. These findings are important as they offer a promising avenue for developing novel therapeutic strategies targeting TAM.